From Hyposociability to Hypersociability—The Effects of PSD-95 Deficiency on the Dysfunctional Development of Social Behavior - Gao, Wen-Jun; Mack, Nancy R. (Frontiers in Behavioral Neuroscience, 2021)
Abnormal social behavior, including both hypo- and hypersociability, is often observed in neurodevelopmental disorders such as autism spectrum disorders. However, the mechanisms associated with these two distinct social behavior abnormalities remain unknown. Postsynaptic density protein-95 (PSD-95) is a highly abundant scaffolding protein in the excitatory synapses and an essential regulator of synaptic maturation by binding to NMDA and AMPA receptors. The DLG4 gene encodes PSD-95, and it is a risk gene for hypersocial behavior. Interestingly, PSD-95 knockout mice exhibit hyposociability during adolescence but hypersociability in adulthood. The adolescent hyposociability is accompanied with an NMDAR hyperfunction in the medial prefrontal cortex (mPFC), an essential part of the social brain for control of sociability. The maturation of mPFC development is delayed until young adults. However, how PSD-95 deficiency affects the functional maturation of mPFC and its connection with other social brain regions remains uncharacterized. It is especially unknown how PSD-95 knockout drives the switch of social behavior from hypo- to hyper-sociability during adolescent-to-adult development. We propose an NMDAR-dependent developmental switch of hypo- to hyper-sociability. PSD-95 deficiency disrupts NMDAR-mediated synaptic connectivity of mPFC and social brain during development in an age- and pathway-specific manner. By utilizing the PSD-95 deficiency mouse, the mechanisms contributing to both hypo- and hyper-sociability can be studied in the same model. This will allow us to assess both local and long-range connectivity of mPFC and examine how they are involved in the distinct impairments in social behavior and how changes in these connections may mature over time.